DETERMINAN DEBT MATURITY STRUCTURE PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI ISSI PERIODE 2012-2015 - Gianissa Pandu Islamy; Nisful Laila (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research analyzes the influence of firm size, profitability, tangibility, and asset maturity variable to debt maturity structure of consumer goods company in Indonesia. The population of this study consists of companies of industrial goods and consumption listed in Indonesia Sharia Stock Index period 2012-2014. The sample was taken by using purposive sampling method so that obtained 19 companies that fulfill the requirement as a sample. The result of research with Fixed Effect estimation model shows that firm size, profitability, and asset maturity have significant effect to debt maturity structure with a different level of significance. Based on the value of the coefficient of determination (R2) of 92.06% shows that the percentage of the ability of exogenous variables in explaining endogenous variables of 92.06% while the rest of 7.94% explained by other variables outside this study.  REFERENCESAnshori, M., & Iswati. (2009). Buku Ajar Metodologi Penelitian. Surabaya: Airlangga University Press.Barclay, & Smith. (1995). The Maturity Structure of Corporate Debt. Journal of Finance , 50(2): 609-632.Barnea. (1980). A Rationale for Debt Maturity Structure and Call Provisions in the Agency Theoritic Framework. Journal of Finance , 35(5):1233-1234.Brigham, & Houston, F. (2011). Dasar-Dasar Manajemen Keuangan. Jakarta: Salemba Empat.Chiang, Y. (2014). Corporate Governance and The Dynamics of Capital Structure:New Evidence. Journal of Financial Intermediation .Ghozali, I. (2005). Aplikasi Analisis Multivariate dengan Progam SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Gujarati. (2013). Dasar-dasar Ekonometrika (Edisi Kelima ed.). Jakarta: Salemba Empat.Hajiha, & Akhlagi. (2012). The Determinants of Debt Maturity Structure in Iranian Firms. African Journal of Business Management , 1973-1982..Huang, G. (2006). The Determinnats of Capital Structure: Evidence From China. China Economic Review , pp. 14-36.Husnan, S., & E, P. (2012). Dasar-dasar Manajemen Keuangan. Yogyakarta: UPP AMP YKN.Jason, & Hong, Z. (2006). The Financing Behaviour of Listed Chinese Firms. Accounting , 239-258.Jensen, M., & Wiliam. (1976). The Theory of Firm: Managerial Behaviour, Agency Cost and Ownership Structure. Journal of Financial Economic , 305-306.Kasmir. (2013). Analisis Laporan Keuangan. Jakarta: Raja Grafindo Persada.Leland, T. (1996). Optimal Capital Structur, Endogeneous Bankruptcy and Term Structure of Credit Spreads. Finance Journal , 987-1019.Mai, M. (2006). Analisis Variabel-variabel yang Mempengaruhi Struktur Modal pada Perusahaan-perusahaan LQ45 di Bursa Efek Jakarta. Tirtayasa Ekonometrika, 2, 228-245.Modigliani, F., & M., H. M. (1963). The Cost of Capital Corporatiom Finance and The Theory of Investment. American Economic Review , 261-297.Myers, S. C. (1977). Determinnats of Corporate Borrowings. Journal Of Financial Economics, 5, 147-175.Modigliani, F., & M., H. M. (1963). The Cost of Capital Corporatiom Finance and The Theory of Investment. American Economic Review , 261-297.Ozkan. (2002). An Empirical of Corporate Debt Maturity Stucture. Europan Financial Management , 6(2):197-212.Pandey, I. M. (2001). Capital Structure and The Term Characteristics: Evidence From An Emerging Market. Journal of Financial , 1-17.Rajan, G. R., & Zingales. (1995). What Do We Know Of Capital Structure? . Journal of Finance , 14121-14160.Sajid, M. (2012). The Determinnats of Corporate Debt Maturity Structure. African Journal of Business Management, 6 (14), 4988-5003.Shihab, Q. (2002). Tafsir Al Mishbah: Pesan, Kesan dan Keserasian Al- Qur'an. Ciputat: Lentera Hati.Soekirman, A. (2015). Determinants of Debt Maturity in Indonesia Firm. IJABER, 13, 5999-6016.Stephan, A. (2011). Corporate Debt Maturity Choice in Emerging Finacial Markets. The Quartly Review of Economics and Finance , 141-151.Stohs, M. H., & Maurer. (1996). The Determinant of Corporate Debt Maturity Structure. Journal of Business , 69:279-312.Sudana, I. M. (2011). Manajemen Keuangan Perusahaan. Surabaya: Erlangga.Sukianto, A. (2013). Faktor- faktor yang Mempengaruhi Debt Maturity di Sektor Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2008-2012. Jurnal Ilmiag Mahasiswa Universitas Surabaya .Terra, P. R. (2011). Determinants of Corporate Debt Maturity in Latin America. Europan Business Review, 23, 45-70.Titman, S., & Wessels, R. (1998). The Determinants of Capital Structure Choice. Journal of Finance, XLIII, 1-19.Weston, Z. F. (1997). Manajemen Keuangan (Edisi Kesembilan ed.). Jakarta: Binarupa Aksara.Widiarjono, A. (2005). Ekonometrika: Teori dan Aplikasi untuk Ekonomi dan Bisnis. Yogyakarta: Ekonisia.Zaini, Z. (2014). Memahami Bisnis Bank Syariah. Jakarta: PT. Gramedia Pustaka Utama.